ESCMID Study Group for Infections in Compromised Hosts (ESGICH) Consensus Document on the safety of targeted and biological therapies: an infectious diseases perspective (Soluble immune effector molecules [I]: anti-tumor necrosis factor-α agents). (June 2018) - Baddley, J.W.; Cantini, F.; Goletti, D.; Gómez-Reino, J.J.; Mylonakis, E.; San-Juan, R.; Fernández-Ruiz, M.; Torre-Cisneros, J.
Abstract: Background: The present review is part of the ESCMID Study Group for Infections in Compromised Hosts (ESGICH) Consensus Document on the safety of targeted and biological therapies. Aims: To review, from an Infectious Diseases perspective, the safety profile of agents targeting tumour necrosis factor-α (TNF-α) and to suggest preventive recommendations. Sources: Computer-based MEDLINE searches with MeSH terms pertaining to each agent or therapeutic family. Content: Preclinical and clinical evidence indicate that anti-TNF-α therapy (infliximab, adalimumab, golimumab, certolizumab pegol and etanercept) is associated with a two-to four-fold increase in the risk of active tuberculosis and other granulomatous conditions (mostly resulting from the reactivation of a latent infection). In addition, it may lead to the occurrence of other serious infections (bacterial, fungal, opportunistic and certain viral infections). These associated risks seem to be lower for etanercept than other agents. Screening for latent tuberculosis infection should be performed before starting anti-TNF-α therapy, followed by anti-tuberculosis therapy if appropriate. Screening for chronic hepatitis B virus (HBV) infection is also recommended, and antiviral prophylaxis may be warranted for hepatitis B surface antigen-positive individuals. No benefit is expected from the use of antibacterial, anti- Pneumocystis or antifungal prophylaxis. Pneumococcal and age-appropriate antiviral vaccinations (i.e. influenza) should be administered. Live-virus vaccines (i.e. varicella-zoster virus or measles–mumps–rubella) may be contraindicated in people receiving anti-TNF-α therapy, although additional data are needed before definitive recommendations can be made. Implications: Prevention measures should be implemented to reduce the risk of latent tuberculosis or HBV reactivation among individuals receiving anti-TNF-α therapy.